The image of Tuva's space in Runet - Bragina, Marina A.; Levina, Vera N. (The New Research of Tuva, 2023)
Each distinct region, both within Russia and globally, is primarily conceived as a territory — a space whose representation is crafted through diverse informational and communicative channels. The present article undertakes an analysis of creolized texts within the Russian-language segment of the internet pertaining to travel experiences in the Republic of Tuva from 2020 to 2023. The primary objective of this research is to delineate the verbal and non-verbal mechanisms employed in shaping the image of the Republic of Tuva as a distinctive region within Russia, within the context of polycode Russian-language internet texts on travel, encompassing genres such as blogs, posts, and websites. These texts are authored by individuals who share their impressions and emotions regarding their journeys to this particular region.The research methodology is grounded in functional-semantic and structural-semantic approaches, facilitating a comprehensive analysis of empirical material and the identification of means employed in representing the image of Tuva, key linguistic units, and their associated semantics.Throughout the course of the study, diverse creolized texts on travels to the Republic of Tuva were discerned within the Russian-language internet segment. These texts exhibit structural and semantic variances, encompassing travel reviews, blogger interviews, writings by professional travel journalists, impressionistic poetic compositions, and video sketches. In these works, the virtual representation of Tuva as a unique natural expanse is constructed through the utilization of lexical units imbued with landscape semantics, succinct grammatical-syntactic constructions, the establishment of associative series, and other verbal and non-verbal modalities (comprising audio and video elements, as well as photographic illustrations).
Keywords: Tuva; Republic of Tuva; space; internet text; functional-semantic approach; landscape semantics